Implementation of Teams Games Tournament Cooperative Learning to Develop Cooperative Skills - Karina Puji Lestari; Fu’adah, Laily; Kurniawan, Nofan Adi (Edukasi, 2024)
Cooperation has become an important skill in modern education, which emphasizes the development of social skills and soft skills in addition to the mastery of knowledge. This study aims to assess the application of the Teams Games Tournament type cooperative learning method in developing the cooperation skills of grade VII F students at SMP 3 Kudus. Using a classroom action research method with the Kemmis and Taggart model, this research goes through four stages: planning, implementation, observation, and reflection, the results of which are analyzed to determine the next step. A total of 30 students from class VII F at SMP 3 Kudus were involved as subjects of this study. Data collection techniques include interviews, observations, and documentation. The results of the study show that the Learning Implementation Plan (RPP) with the Teams Games Tournament cooperative model  in grade VII F SMP 3 Kudus has been prepared in accordance with the Regulation of the Minister of Education and Culture No. 12 of 2024, with an increase in time management and the use of learning media in cycle II. The application of this method has succeeded in increasing student involvement in cooperation, where teachers play the role of facilitators in learning. This study recorded an increase in students' cooperation skills from an average of 62.7% in the first cycle to 80.1% in the second cycle, showing an increase of 17.4%. The findings of this research provide practical benefits for educators by demonstrating an effective approach to fostering cooperation skills through the TGT cooperative learning model. Moreover, the study contributes to the enrichment of pedagogical strategies that align with modern educational demands, helping to create an interactive and student-centered learning environment. This research also serves as a reference for future studies aiming to explore innovative teaching methods to enhance soft skills in secondary education settings.